The influence of social media on the obsession with healthy eating in adolescents (Research, Society and Development, 2024)
Introduction: The term Orthorexia Nervosa is defined as the obsession and fixation on eating healthy foods, to the point of becoming pathological. The profile of vulnerable individuals includes people who are meticulous, organized and with an exacerbated need for self-care or protection. This group may include women, teenagers, people who follow food fads and athletes. The concern with adolescents stands out, as at this stage there are intense changes in the organism and in life and issues related to nutrition deserve attention. Objective: Identify factors related to Orthorexia in adolescents. Methods: A narrative literature review was carried out between August and October 2023 with a search for articles in the databases: Scientific Electronic Library Online (SciELO), Google Scholar, US National Library of Medicine (MEDLINE/PubMed), Virtual Library of Health (VHL) and ScienceDirect. As inclusion criteria, original articles referring to the topic were selected, available free of charge in full, in English, Spanish and Portuguese. Discussion: Some vulnerable groups were identified in the studies, among which adolescents stand out. Furthermore, it was pointed out that social media has a great impact on the perception that adolescents have about their own bodies, resulting in excessive healthy eating triggering symptoms of ON. Conclusion: Social media can intensify depressive symptoms and disorders, especially in adolescence. The difficulty associated with Orthorexia is differentiating the individual who prioritizes healthy eating habits from the one who presents obsessive behavior. Studies are still scarce on Orthorexia Nervosa and therefore, there is a need for more research on the topic.